Study of hysteroscopic evaluation in patients with abnormal uterine bleeding - K., Ashok Kumar; P., Sathya; Sampathkumar, Sreelatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding in women is the commonest presenting complaint which accounts for one third of all gynecological consultations. It not only causes discomfort, inconvenience to healthy women but also affects their quality of life and impose financial burden on them. This insists the physician to diagnose its etiology and provide appropriate treatment. Hysteroscopy guided biopsy is a simple, safe, reliable procedure in the diagnosis of abnormal uterine bleeding. The objective of the study was to evaluate the uterine pathology in premenopausal women with abnormal uterine bleeding by hysteroscopy. Methods: This prospective study was conducted at ESIC-MC and PGIMSR, Rajajinagar, Bangalore, in 50 premenopausal women with abnormal uterine bleeding over 18 months from Dec 2012 to May 2014. All 50 women were subjected to diagnostic hysteroscopy followed by curettage. The sample was sent to histopathological examination. Data was collected and analyzed. Results: In the present study, abnormal uterine bleeding was more common in 41-45yrs of age. The commonest presenting complaint was heavy menstrual bleeding (menorrhagia) in 54% of cases. The abnormal findings on hysteroscopy were: Hyperplasia 42%, endometrial polyp 22%, sub-mucous myoma 4%, carcinoma endometrium 2%, synechiae 2% and endometritis 2%. Negative hysteroscopic view was seen in 26%. The sensitivity, specificity, positive and negative predictive value of hysteroscopy was 91.89%, 92.31%, 97.14% and 80% respectively. The overall diagnostic accuracy of hysteroscopy was 92%. Conclusions: Hysteroscopy and its directed biopsy renders high diagnostic accuracy in patients with abnormal uterine bleeding and thereby guiding them for further management.